Characterization of topologically close-packed phases and precipitation behavior of P phase in a Ni-based single crystal superalloy. (October 2020) - Zhang, Youjian; Zhang, Jianxin; Li, Pan; Jin, Huixin; Zhang, Wenyang; Wang, Zihan; Mao, Shengcheng
Abstract: Scanning electron microscopes (SEM) and transmission electron microscopes (TEM) were employed to investigate the topologically close-packed (TCP) phases in an experimental nickel base single crystal superalloy. Orientation relationships between P phase and matrix were found as (010)P //(1 1 ‾ 1)γ and [201]P //[110]γ, in which atomic arrangement of P phase obtains the optimal matching with that of γ/γ' matrix and the semi-coherent interface forms, achieving the lower interface energy. The elemental composition, atomic arrangement of low index planes and the atomic attachment of P phase with matrix were analyzed in detail to investigate the atomic scale structure of the fast-growing semi-coherent interface and its effects on precipitate growth. Finally, the nucleation of P phase was discussed. Highlights: μ and P phase were characterized by electron microscopes. HRTEM micrographs and orientation relationships imply the semi-coherent P/γ interface. Atomic attachment of P phase with matrix was discussed. The nucleation of P phase was discussed.